Firm Characteristic’s and Shareholder Wealth Effects: An Acquiring Firm perspective in India for Cross-border and Domestic Acquisitions - Rama Bhadran Shamala, Srikanth (2011)
I analyse, what is the differences in abnormal returns to acquiring firm shareholders for cross-border and domestic acquisitions in India? Does the acquiring firm characteristics have a significant impact on acquiring firm’s shareholder wealth for both cross-border and domestic acquisitions? For the purpose of this study I have collected a total sample of 200 Indian acquiring companies, comprising of 100 cross-border acquiring companies and 100 domestic acquiring companies respectively, for the period 2000-2008. Using the mean values of CAR I have documented that for acquirers in India, cross-border acquisitions are more beneficial than domestic acquisitions. Using CAR, financial, growth, size, free cash flow and management variables I have found evidence that acquiring firm characteristic’s have a significant impact on acquiring firm’s shareholder wealth.